2007
DOI: 10.1111/j.1365-2036.2006.03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease and the risk of fractures – a general population‐based cohort study

Abstract: SUMMARY BackgroundEarlier studies have suggested that untreated coeliac disease may be associated with osteoporosis, but results are contradictory for the risk of long-term fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
3
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 50 publications
4
120
3
4
Order By: Relevance
“…This risk is greater than that reported in a study from England [47], while it is similar to the risk of first hip fractures in Swedish children with celiac disease [48]. In this population-based study, we demonstrate that fracture risk is, in fact, elevated among patients with celiac disease.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This risk is greater than that reported in a study from England [47], while it is similar to the risk of first hip fractures in Swedish children with celiac disease [48]. In this population-based study, we demonstrate that fracture risk is, in fact, elevated among patients with celiac disease.…”
Section: Discussionsupporting
confidence: 65%
“…Most significantly, the increase in fracture risk persists after the diagnosis of celiac disease. This suggests the bone disease at diagnosis is often sufficiently advanced as to preclude a return to health even with subsequent diet restriction and medical management [47][48][49]. It is also possible that the persistent risk of fractures is due to other factors such as muscle weakness or neurologic disturbance, though that would not necessarily explain the trend for increased frequencies of spontaneous and axial fractures in the celiac cases.…”
Section: Discussionmentioning
confidence: 99%
“…CD is associated with an increased risk of fractures, [154][155][156] with relative risks of around 2 for fractures after CD diagnosis. An earlier study found a similar relationship (odds ratio around 2) for fractures prior to diagnosis, in patients with CD.…”
Section: Qol Aspects Of Screening For CDmentioning
confidence: 99%
“…Moreover, CD associates with metabolic bone disease. The frequency of low bone mineral density (BMD) among coeliac patients varies widely between different studies due to differences in diagnostic criteria, geographical distribution and patient selection (12)(13)(14). The presence of significant malabsorption leads to a more severe bone loss in CD (15), although BMD is lower in asymptomatic patients compared to healthy subjects, as well (16).…”
Section: K Lorinczy Et Al Rev Esp Enferm Dig (Madrid)mentioning
confidence: 99%